2018
DOI: 10.5603/nmr.a2018.0010
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation in Dextrocardia on myocardial perfusion imaging: how to perform quantitative analysis using Cedars-Sinai software

Abstract: Dextrocardia, although a rare cardiac abnormality, carries the same risk for cardiac events as other people. SPECT Myocardial perfusion imaging is a potentially helpful diagnostic tool in patients with dextrocardia. Due to swapping of lateral and septal walls on SPECT slices, although visual analysis is possible, quantitation is substantially limited. Here, we introduce a simple practical method to make quantitative analysis feasible and accurate. Case reportA 50-year-old male patient with known history of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 3 publications
(5 reference statements)
0
3
0
3
Order By: Relevance
“…Ayeni et al acquired MPS images of situs inversus totalis using feet-in supine positioning and 2 processing methods; the second method applied feet-first prone positioning, which was entered in the processing software and allowed the lateral wall and septum to be reconstructed in the normal axis (3). Qutbi et al suggested a change from feet-in during acquisition to head-in or prone during processing to correct the orientation of the lateral wall and septum (5,6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ayeni et al acquired MPS images of situs inversus totalis using feet-in supine positioning and 2 processing methods; the second method applied feet-first prone positioning, which was entered in the processing software and allowed the lateral wall and septum to be reconstructed in the normal axis (3). Qutbi et al suggested a change from feet-in during acquisition to head-in or prone during processing to correct the orientation of the lateral wall and septum (5,6).…”
Section: Discussionmentioning
confidence: 99%
“…Many case reports have provided guidance about positioning and image processing using MPS in dextrocardia patients (3)(4)(5)(6)(7)(8)(9); however, there are fewer reports on assessing myocardial viability using 18 F-FDG PET.…”
mentioning
confidence: 99%
“…Apabila pada pasien ini dilakukan modifikasi protokol dengan kepala mengarah ke dalam (head in) maka gambaran perfusi yang dihasilkan sama interpretasinya dengan populasi dengan letak jantung normal, namun memerlukan suatu perangkat lunak (software) yang khusus untuk pasien dekstrokardia. [16][17][18] Pemeriksaan SPM menunjukan adan ya defek perfusi parsial reversibel pada se bagian apeks, segmen apiko septal, segmen apiko-mid anterior, dan apiko-basal infero-lat eral. Summed stress score adalah 11, summed rest score 2, dan summed difference score 9.…”
Section: Laporan Kasusunclassified
“…Apabi la pemeriksaan dilakukan dengan modifika si protokol, yaitu posisi kepala mengarah ke dalam alat (head in) maka citra perfusi dan interpretasi yang dihasilkan akan sama den gan populasi umum (Gambar 6), namun me merlukan suatu perangkat lunak (software) yang khusus untuk pasien dekstrokardia. [16][17][18] Beberapa kamera gamma dapat mempunyai perangkat lunak yang berguna untuk akuisi si dan interpretasi dekstrokardia. Protokol ini harus dilakukan dengan baik dan benar agar tidak terjadi kesalahan interpretasi dalam me nentukan dinding lateral dan dinding septal ventrikel kiri.…”
Section: Diskusiunclassified
See 1 more Smart Citation